2000
DOI: 10.1097/00005373-200001000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhalation of Corticosteroids Immediately after Experimental Chlorine Gas Lung Injury

Abstract: Immediate treatment with nebulized BDP improved pulmonary and cardiovascular function after experimental chlorine gas injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…The risk of exposure to chlorine gas with many casualties is widespread, since chlorine is carried through densely populated areas in large quantities (Gunnarsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of exposure to chlorine gas with many casualties is widespread, since chlorine is carried through densely populated areas in large quantities (Gunnarsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we did not use corticosteroids in the present case. In animal experimental studies, systemic or inhaled corticosteroids showed benefits in pulmonary function recovery immediately after chlorine exposure (13)(14)(15)(16). In a previous case report, the clinical manifestations demonstrated improvement within 5 days with corticosteroid administration (17).…”
Section: Discussionmentioning
confidence: 91%
“…They are postulated to abate the inflammatory response, countering the chlorine-mediated decrease in lung compliance and gas exchange, and to be particularly useful in patients with underlying reactive airway disease. However, while there are good data from studies in pigs to suggest effectiveness of this therapy, there is only anecdotal evidence in humans [21][22][23][24].…”
Section: Case Continuationmentioning
confidence: 99%